2013
DOI: 10.1145/2414446.2414449
|View full text |Cite
|
Sign up to set email alerts
|

Implementing an affordable high-performance computing for teaching-oriented computer science curriculum

Abstract: The main objective of this poster is to present an affordable and easy-to-use high performance cluster system that can be used for the classroom in teaching-oriented computer science curriculum. In order to address this, we design and implement an affordable high performance cluster system that is based on PlayStation 3  . PS3 is a well-known for game console manufactured by Sony. Since each PS3 console has IBM Cell BE processor that consists of 8 Synergistic Processing Elements (SPEs) and 1 Power Processing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
(5 reference statements)
0
7
0
Order By: Relevance
“…Several authors have addressed the logistical challenge of procuring an HPC platform for educational purposes by establishing low-cost such platforms [1]- [6] or by using virtualization and/or container technology [7]- [10]. Although these solutions offer compelling capabilities, such as exposing students to real-world software infrastructures, they impose limits on platform scale and/or may not be representative of production HPC platforms, especially in terms of performance behaviors.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have addressed the logistical challenge of procuring an HPC platform for educational purposes by establishing low-cost such platforms [1]- [6] or by using virtualization and/or container technology [7]- [10]. Although these solutions offer compelling capabilities, such as exposing students to real-world software infrastructures, they impose limits on platform scale and/or may not be representative of production HPC platforms, especially in terms of performance behaviors.…”
Section: Related Workmentioning
confidence: 99%
“…For some institutions, it may be that no HPC platform is available whatsoever. In this case, one can resort to building lowcost HPC platforms for teaching purposes [1]- [6], to using virtualization and/or container technology to emulate an HPC platform, e.g., in cloud environments [7]- [10], or to gain access to public HPC testbeds. Although a lot can be achieved pedagogically on such platforms, they are not necessarily representative of production HPC platforms (in terms of capabilities, scale, and/or performance behaviors), which can be problematic for performance-oriented learning objectives.…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that with the increasing of the total number of processor could shortened the computational time. The main control process happens in server node which has a job to deviding the number of process and scatter the grayscale colour value to 2,4,8,16, and 32 processors. Process node will execute the fft to those part of pixel data that sended from server node.…”
Section: Image Processing Testing and Analysismentioning
confidence: 99%
“…Other solutions, virtualized parallel resources on non parallel hardware are typically free or low cost, highly available and have good turnaround, but may have misleading performance characteristics due to limited physical parallelism. Therefore, cluster computing is the best alternative way to build a high performance computing platform with low cost to give HPC learning for students in university [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…This training has to face the limitations of the integration of technologies in teaching [44,47] and at the same time be included in the standard curriculum as a constraint related with Supercomputing [26]. Currently, the use of Supercomputers is becoming a key element in the improvement of certain disciplines of higher education, in spite of the lack of experience and basic skills in this field [1] and low availability of Supercomputing facilities due to the high costs [19].…”
Section: Introductionmentioning
confidence: 99%